High-Pressure Processing of Fruit Smoothies Enriched with Dietary Fiber from Carrot Discards: Effects on the Contents and Bioaccessibilities of Carotenoids and Vitamin E - Donda Zbinden, Melisa Elisabet (2024)
The effects of high-pressure processing (HPP) (450 MPa/600 MPa/3 min) on the carotenoidand vitamin E contents of smoothies made from strawberry, orange juice, banana and apple, and thesame smoothies enriched with dietary fiber from discarded carrots were compared. The contentsand bioaccessibilities of these compounds were also evaluated over the course of 28 days at 4 ◦C.The application of HPP in the formulations significantly increased the contents of β-cryptoxanthin,α-carotene and β-carotene and retained the contents of lutein, zeaxanthin and vitamin E comparedto untreated samples. A decreasing trend in the content of each compound was observed with anincrease in storage time. The application of HPP initially led to reductions in the bioaccessibility ofindividual compounds. However, overall, during storage, there was an increase in bioaccessibility.This suggests that HPP influences cell structure, favoring compound release and micelle formation.HPP is a sustainable method that preserves or enhances carotenoid extractability in ready-to-drinkfruit beverages. Furthermore, the incorporation of dietary fiber from carrot processing discardssupports circular economy practices and enhances the health potential of the product.